243 Sensory Processing of Children with Autism: Uniting Evidence and Practice. (October 2012) - Ayyash, HF; Barrett, E; Ogundele, M
Abstract : Background: Sensory processing function is the child's ability to register, modulate and discriminate between different sensory information arising from the body (e.g. tactile and vestibular sense) and those received from the environment (vision, auditory and gustatory senses). Individuals with autism commonly experience sensory processing difficulties, which can impact upon functional performance in activities of daily living. Aim: To investigate the sensory processing patterns of children with autism. Methods: 15 children aged between 4 to 10 years old (Average 6.9 years) who were diagnosed with autism were included in the study. Their parents/carers completed the Sensory Profile Caregiver's Questionnaire. This is a standardised tool designed to assess children's sensory processing dysfunction in their daily functional performance. Results: There were 13 boys and 2 girls. Nine children were attending mainstream schools and six attended special schools. The assessments completed highlighted that all children experienced some form of sensory processing difficulty (Figure 1 ). Conclusion: The findings support the key theme found in literature indicating that individuals with autism commonly experience sensory processing difficulties. There seem to be clear links between sensory processing difficulties and reduced functional performance during school and home activities. Further controlled studies on sensory processing in children with autism are recommended.